Correlation of the Handgrip Strength and Body Composition Parameters in Young Judokas - Tavares Junior, Antonio Carlos [UNESP]; Silva, Henrique Santos [UNESP]; Penedo, Tiago [UNESP]; do Amaral Rocha, Leandro George Spínola [UNESP]; da Silva, Alexsandro Santos [UNESP]; Venditti Junior, Rubens [UNESP]; Dos-Santos, Júlio Wilson [UNESP] (MDPI, 2023)
Maximum isometric handgrip strength (MIHS) is a relevant parameter for judo performance and is related to health. Understanding the association between MIHS and MIHS relative (MIHSrel) and the absolute lean mass of the arm (LMarm) and the percentage of body fat (%BF) can provide important information for performance and health. The study aimed to investigate the correlation between MIHS and MIHSrel with the LMarm and the %BF of young judokas (sub-19, 15 males and 14 females). MIHS was measured using a multipurpose digital dynamometer with a load cell for computer. Body composition was measured by dual-energy X-ray absorptiometry (DXA). The correlation between MIHS, MIHSrel with LMarm and %BF was verified through Pearson’s correlation, with a significance level of p < 0.05. Correlation between MIHSrel and %BF was very high only in female judokas for both arms (right, r = −0.76; left, r = −0.75). Correlations between LMarm and MIHS of the right and left arms ranged from very high to almost perfect for both sexes (r = 0.74 to 0.94). These results highlight the importance of strengthening the arms in young judokas, and controlling body fat for performance and health, especially in female judokas.
Keywords: athletic performance; dual X-ray absorptiometry; hand strength; martial arts; youth sports